2013
DOI: 10.1016/j.bbadis.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac matrix: A clue for future therapy

Abstract: Cardiac muscle is unique because it contracts ceaselessly throughout the life and is highly resistant to fatigue. The marvelous nature of the cardiac muscle is attributed to its matrix that maintains structural and functional integrity and provides ambient micro-environment required for mechanical, cellular and molecular activities in the heart. Cardiac matrix dictates the endothelium-myocyte (E-M) coupling and contractility of cardiomyocytes. The Matrix metalloproteinases (MMPs) and their tissue inhibitor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 75 publications
(118 reference statements)
2
48
0
Order By: Relevance
“…In the heart, miRNAs are involved both in cardiogenesis (14,15) and in disease including: diabetic cardiomyopathy, hypertrophy, ischemia, and electrical remodeling (16 -22). Recent developments in both therapeutic inhibition and enhancement of miRNA function have demonstrated great promise for counteracting cardiac diseases (22,23). However, the off-target effects of miRNAs and antisense oligonucleotides that target miRNAs (i.e.…”
mentioning
confidence: 99%
“…In the heart, miRNAs are involved both in cardiogenesis (14,15) and in disease including: diabetic cardiomyopathy, hypertrophy, ischemia, and electrical remodeling (16 -22). Recent developments in both therapeutic inhibition and enhancement of miRNA function have demonstrated great promise for counteracting cardiac diseases (22,23). However, the off-target effects of miRNAs and antisense oligonucleotides that target miRNAs (i.e.…”
mentioning
confidence: 99%
“…Early-stage aortic banding results in inhibition of MMP9, but sustained mechanical overload causes de-compensatory heart failure, leading to increased MMP9 expression and cardiac fibrosis in end-stage heart failure. As aforementioned, activation of MMP9 increases extracellular matrix turnover in the failing heart, 50 resulting in increased apoptotic signaling in pressure overload heart failure (Mishra et al 2013 Fujino et al 2012). Within TFAM over-expression models, it is observed that proteolytic enzyme MMP9 is reduced in MI-induced HF, along with functional morphologies (Ikeuchi et al 2005).…”
Section: Nadph Oxidases To Increase Ros Production (Williams and Goocmentioning
confidence: 91%
“…MMP9 is a distinguishing factor in pathological cardiac remodeling (Mishra et al 2013). This observation correlates with known studies showing that increased activation of MMPs is observed in TFAM ablation and oxidative stress models (Larsson et al 1998;Lamparter and Maisch 2000).…”
Section: Chapter V Discussion Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations